Media framing of ZANU PF Internal Succession Struggles: Mnangagwa and the Military Factor - Mungwari, Teddy (American Journal of Social Sciences and Humanities, 2018)
This article discusses the representation of the ruling party, Zimbabwe African National Union Patriotic Front (ZANU PF) internal succession battles, particularly presidential succession. The paper argues that two factions within ZANU PF, Team Lacoste (a faction that backed Mnangagwa to succeed Mugabe) and G40 (a faction that supported Grace Mugabe to take over Presidency) fought fierce battles which the media extensively reported on. The article also argues that Grace’s overwhelming ambition to succeed her husband, Robert Mugabe, led to the events where she publicly attacked Emmerson Mnangagwa until Mugabe fired him. Mnangagwa’s dismissal from the post of Vice President precipitated dramatic events that led to the ‘military coup’ or intervention on 15 November 2017. It was widely believed that Mnangagwa enjoyed the support of the country’s securocrats (military uniformed forces nexus), who include the country’s military, intelligence and the former liberation war fighters. This article further argues that the ‘military coup’ was a long planned strategy which began in 2008 but was brewing until it was finally triggered by the dismissal of Mnangagwa. The Zimbabwean electronic, print and social media platforms as well as foreign media actively covered the succession struggles. However, this paper only analysed the state-controlled daily, The Herald, and two daily privately owned newspapers Daily News and News Day, to examine how they framed the internal succession battles from October to December 2017. The three newspapers have diverse editorial and ideological agendas. The article concluded that The Herald, which is pro-government and ruling party, was torn-in-between Mugabe and Mnangagwa. News reporters were in a crisis on how to cover the events, especially from 13-15 November 2017, until state capture of strategic institutions by the military. However, privately owned newspapers maintained their middle of the road approach in covering the events. The paper can argue that state-controlled media’s ideological and editorial policies may change to suit interests of those in power thereby compromising ethical reportage. The article also concluded that Zimbabwe’s new dispensation is characterised by militarisation of state institutions with many key posts occupied by retired military personnel; which arguably may lead to manipulation of 2018 general elections. There is systematic purging of all perceived G40 members, (who are labeled as cabalists by Team Lacoste), including top civilian CIO members by Mnangagwa’s administration which is allegedly guided by Military Intelligence. ZANU PF succession politics may be far from being over as G40 members might be planning a comeback – only time will tell.